- 1-800-665-6601
- [email protected]

form of ax^2+bx+c=0, Here ‘a’ is the coefficient of x ^2, ‘b’ is the coefficient of x and c is the constant number.

To factor a polynomial equation, break the expression as multiples of two expressions.

Solution steps:

Sum of terms = x

So we want two numbers that add up to get x, and multiply together to make -12.

In fact -3 and 4 do that (-3x + 4x = x, and -3 × 4 = -12)

Rewrite x with -3x and 4x:

6x

The first two terms 6x

The last two terms 4x - 2 factor into 2(2x - 1)

So we get 3x (2x - 1) + 2(2x - 1)

3x(2x - 1) + 2(2x - 1) = (3x + 2)(2x - 1)

Solution steps:

Sum of terms =7xy

so we want two numbers that add up to 7, and multiply together to make -120.

In fact -8 and 15 do that: -8xy + 15xy = 7xy, and -8 × 15 = -120

Rewrite 7xy with -8xy and 15xy:

6x